Safer Attitude to Risky Decision-Making in Premanifest Huntington’s Disease Subjects - D’Aurizio, Giulia; Migliore, Simone; Curcio, Giuseppe; Squitieri, Ferdinando (Frontiers in Psychology, 2019)
Huntington’s disease (HD) is an inherited neurodegenerative disorder characterized by involuntary, jerky movements, incoordination, behavioural changes and subtle executive and cognitive impairment starting before motor symptoms. Our study aimed to assess the risky decision-making process in premanifest (pre) HD subjects, by means Game of Dice Task (GDT). As dependent variables, several Game of Dice Task outcomes have been taken into consideration. We recruited 30 subjects (15 females) with preHD (i.e. Diagnosis Confidence Level <4; Total Motor Score <10), and 21 age, gender and education matched neurologically normal subjects (11 females). Game od Dice Task is a computer-guided task where subjects are invited to watch the digits on which to bet and to evaluate the related potential risk to win or loss. Our results showed that decision and feedback times were longer in preHD than in neurologically normal group in both disadvantageous and advantageous choices. PreHD subjects provided a greater number of "safe" strategies, taken with longer decision-making time than neurologically normal subjects, showing a reduced propensity to risk. Such behaviour, characterized by increased slowness in acting and providing answers, might contribute to delineate a behavioural and cognitive profile in preHD.